Tracking of pendulum by particle smoother - RamVemuri, Mohan; BinduBade, Hima; Rao.S, Koteswara; Gopi Tilak, V (International Journal of Engineering and Technology, 2018)
The series of tracking algorithms accelerated from linear state to non-linear state estimations like the Particle filter.Due to its vibrant computation,tracking signal gets divergedat peaks.Smoothing makes perfect estimation possible, even at that minute portions by modifying its trace based on all the prior measurement values.So, a Particle smoother is used which uses Monte Carlo approximations for smoothing in a non-linear system. Different types of Particle Smoothers can be implemented by using various algorithms. Here, a Backward Simulation Particle smoother is used which is relatively less degenerate than other smoothing algorithms.